BRIDGING ENVIRONMENTAL IMPACT OF FOSSIL FUEL ENERGY: THE CONTRIBUTING ROLE OF ALTERNATIVE ENERGY - ADEKOMAYA OLUDAISI; ADAMA KAYODE; OKUBANJO AYODEJI (Journal of Engineering Studies and Research)
The demand for fossil fuel energy remains high amid challenges as it relates to its sustainability among the developing countries of the world. Nigeria remains one of the top consumption of fossil fuel energy considering the large deposit of hydrocarbon in some parts of the country. This energy has been widely used globally with attendant implication on climate and environmental crisis. In this study, attempts were made to portray the environmental impact of fossil fuel energy with attendant effect on global temperature and rising water level. Global warming, among other effect of climate change is now noticeable in all facet of the universe and key of the methodology employed in this work is to assess the existing mitigating strategy and recommend long-lasting approach as it relates to efficient energy use. Key of the conclusion from this work futures the development of municipal solid waste (MSW) as sustainable energy fuel.